Uso de focus groups en investigación científica: Guía práctica para investigadores - Sanz-Marcos, Paloma (Infonomy, 2025)
This article offers a practical guide for researchers new to the qualitative technique of focus groups. Exploring their application, advantages and limitations, it provides a series of detailed recommendations for its correct implementation. Its objective is to serve as a useful tool for those seeking to understand and apply this technique.
Keywords: Focus groups; Methodology; Qualitative; Interviews; Research design; Research technique; Conversation; Group dynamics; Moderator; Groups